2010
DOI: 10.1145/1658349.1658356
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional scaling analysis of haptic exploratory procedures

Abstract: Previous work in real and virtual settings has shown that the way in which we interact with objects plays a fundamental role in the way we perceive them. This paper uses multidimensional scaling (MDS) analysis to further characterize and quantify the effects of using different haptic exploratory procedures (EPs) on perceptual representations. In Experiment 1, twenty subjects rated similarity on a set of nine novel, 3D objects varying in shape and texture after either following their contours, laterally rubbing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
1
7
0
1
Order By: Relevance
“…Cooke et al (2007; see also Cooke et al 2010) reported that multidimensional scaling analyses using similarity ratings from 3-D novel objects indicated that texture and shape information were similarly important for haptics, whereas shape cues were much more important than texture cues for vision (see also Lakatos and Marks 1999). This is consistent with Klatzky et al's (1985) suggestion that extra non-shape cues might explain much of the recognition benefit for 3-D over raised-line drawings.…”
supporting
confidence: 59%
“…Cooke et al (2007; see also Cooke et al 2010) reported that multidimensional scaling analyses using similarity ratings from 3-D novel objects indicated that texture and shape information were similarly important for haptics, whereas shape cues were much more important than texture cues for vision (see also Lakatos and Marks 1999). This is consistent with Klatzky et al's (1985) suggestion that extra non-shape cues might explain much of the recognition benefit for 3-D over raised-line drawings.…”
supporting
confidence: 59%
“…Furthermore, the way in which static (parallel) information and dynamic (serial) touch measure and weigh shape cues is highly similar 3 . A high correlation in the weighing of texture and shape cues for discriminating objects was also shown for such different exploratory procedures as contour following (serial exploration) and gripping (parallel exploration) 2 . Such similar weighting across exploration modes is useful for building stable high-level viewpoint-independent shape representations across the senses, as have been shown for vision and touch 31 32 33 34 .…”
Section: Discussionmentioning
confidence: 74%
“…This is true at least when sampling occurs globally (i.e. along a large portion of the object) and not only locally 1 2 . Moreover, the Parallel and Serial Exploration modes have been shown to assess the same low-level object features, such as local surface slant, for determining object shape 3 .…”
mentioning
confidence: 99%
“…The discrimination thresholds in active touch for both shape and roughness perception were found to be higher when the respective discrimination task was unexpected, compared to conditions in which the task was expected 8 . The emphasis of shape versus texture perception also depends on the exploration procedures which were applied 9 .…”
mentioning
confidence: 99%